Hukum Islam Analisis 'Urf Pengaruh Stratifikasi Sosial terhadap Pemilhan Pasangan Nikah di Desa Tanah Toa, Kajang, Bulukumba: Study Kasus di Desa Tanah Toa, Kecamatan Kajang, Kabupaten Bulukumba - Azis, Nurhidayanti; Syahrezi, Ikhsan; Ma'ruf, Syarif Ma'arif (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This study aims to analyze the influence of social stratification on the selection of marriage partners in the perspective of 'urf in Tanah Toa Village, Kajang District, Bulukumba Regency. The indigenous people of Ammatoa are known to have a strong social structure, which distinguishes between the Puang (nobles) and the Ata (common people), and this has a significant impact on the practice of marriage. This research uses a qualitative method with a theological-normative approach. The main data source is in the form of in-depth interviews with traditional leaders, religious leaders, and local residents. In addition, secondary data were obtained from customary documentation and literature related to social stratification and Islamic law. Data collection techniques are carried out through observation, interviews, and literature studies. The instruments used were a semi-structured interview guide and a voice recording device. Data processing is carried out through the stages of data reduction, data presentation, and conclusion drawn. The analysis was carried out by examining traditional practices and Islamic views on social stratification and inter-caste marriage. The results of the study showed that social stratification affects marriage patterns, where the Puang group tends to marry fellow Puang to maintain social status and lineage. Inter-caste marriages, such as those between Puang and Ata, although customarily possible, are often rejected by families and communities. This norm comes from a long-standing custom. In the perspective of Islamic law, the prohibition is considered 'urf fasid because it is contrary to the principles of justice and equality, which judge a person's glory based on piety, not social status. Islam also gives freedom in choosing a partner as long as it is based on faith and morals. Therefore, in the context of changing social dynamics, this prohibition needs to be reviewed so as not to cause injustice in the socio-religious life of the community.